2019
DOI: 10.1016/j.jebo.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Joint culpability: The effects of medical marijuana laws on crime

Abstract: Most U.S. states have passed medical marijuana laws. In this paper, we study the effects of these laws on violent and property crime. We first estimate fixed effects models that control for flexible city-specific time trends. To supplement this regression analysis, we use the synthetic control method which can relax the parallel trend assumption and better account for heterogeneous policy effects. Both the regression analysis and the synthetic control method suggest no causal effects of medical marijuana laws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Several studies explored the impact of state medical cannabis legalisation on violent and property crime [24][25][26][27] with one noting significant reductions [25]. Other studies report reductions in subsets of the data; for example, Chu and Townsend [27] noted that California experienced a significant reduction (by 20%), Morris et al [26] observed a slight but significant reduction in state homicides, and Gavrilova et al [24] detected significantly reduced crime in states bordering Mexico. In terms of non-medical cannabis legalisation, a recent study examined crime rates in counties along the Washington-Oregon border before and after legalisation in Washington, and noted significant drops in rape and property crime in Washingtonside counties relative to Oregon-side counties [28].…”
Section: Public Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies explored the impact of state medical cannabis legalisation on violent and property crime [24][25][26][27] with one noting significant reductions [25]. Other studies report reductions in subsets of the data; for example, Chu and Townsend [27] noted that California experienced a significant reduction (by 20%), Morris et al [26] observed a slight but significant reduction in state homicides, and Gavrilova et al [24] detected significantly reduced crime in states bordering Mexico. In terms of non-medical cannabis legalisation, a recent study examined crime rates in counties along the Washington-Oregon border before and after legalisation in Washington, and noted significant drops in rape and property crime in Washingtonside counties relative to Oregon-side counties [28].…”
Section: Public Safetymentioning
confidence: 99%
“…Mixed findings for retail sales sites, with some evidence of a reduction in violent crime [29] and other evidence of no significant impact [30] in Denver, Colorado. Medical cannabis legalisation: State medical cannabis laws associated with significant reductions [25] or no change [24,26,27]. Evidence of reductions in states bordering Mexico [24,27], and some evidence of reduction in homicide rate [26].…”
Section: Number and Incidence Of All-cause Motor Vehicle Crash Injurimentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to thank Mirco Tonin for helpful comments on the thesis, Javier Gardeazabal for insightful discussions about the synthetic control methodology and two referees for excellent suggestions on how to improve the paper. Zambiasi Hansen, Miller, and Weber 2019), and crime (Chu and Townsend 2019;Dragone et al 2017). One so far unexamined question has been whether individuals, on average, view the legalization of marijuana as a positive or negative amenity and whether this has led to changes in individuals' migration decisions and the spatial equilibrium of the U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, without a sufficiently large number of policy changes, the estimated standard errors for provision‐specific indicators reported in the current literature are probably biased . In general, a synthetic control approach could be a useful technique, as it is more flexible than the standard fixed‐effects regression analysis .…”
mentioning
confidence: 99%